Assessing Origins of Quality Gaps in Discharge Summaries: A Survey of Resident Physician Attitudes. (20th October 2015) - Otto, Mallory; Sterling, Madeline; Siegler, Eugenia; Eiss, Brian
Abstract : Because little is known about attitudes of primary authors of discharge summaries in academic institutions, namely, trainees and physician assistants (PAs), we sought to explore values, possible areas for improvement, and interest in formal discharge summary education. A survey composed of Likert scale analyses, dichotomous relationships, and open-ended questions was designed using focus groups and validated via expert committee review. Of 135 total residents (PGY 1–3), 79 residents and 10 PAs in a large academic hospital in New York City completed it. Of surveyed trainees, 77.2% reported that quality discharge summaries are useful in primary care. Interns had less outpatient experience with discharge summaries compared to PGY 2 and PGY 3 (23.7% versus 63.4%, p < 0.001 ) and were less comfortable authoring discharge summaries for patients who were not as familiar to them (47.4% versus 24.4%, p = 0.04 ). The majority (54.8%) of interns as well as all PAs reported never receiving feedback on discharge summaries. Finally, 63.2% of interns and 90% of PAs responded that formal teaching would be helpful. Interns' greater discomfort may speak to their poor understanding of core components of a useful discharge summary, which teaching sessions may improve. Alternatively, shifting the authorship responsibility from interns to seniors could be explored as a quality improvement initiative.